Acts of extreme violence and totalitarian Shining Path camps among the Ashaninka and Nomatsiguenga of the central jungle of Peru - Villasante Cervello, Mariella (2024)
Studies on the internal war in Peru have ignored the acts of violence: recruitments, rapes, executions, massacres and totalitarian camps. From the anthropology of violence, this article exposes the central points of an ignored topic: the totalitarian Senderista camps in which thousands of Ashaninka and Nomatsiguenga natives were captives. The Shining Path leaders sought the transformation of thousands of natives who had to destroy their social identities to create a “new communist society.” The priority sources are the testimonies collected by the author between 2008 and 2017, and the testimonies collected by the CVR between 2002 and 2003. The analysis takes into account, in particular, the works of Françoise Héritier, Hannah Arendt, and Tzvetan Todorov.